2018
DOI: 10.1073/pnas.1804992115
|View full text |Cite
|
Sign up to set email alerts
|

Polyprotein strategy for stoichiometric assembly of nitrogen fixation components for synthetic biology

Abstract: SignificanceThe requirement of maintaining balanced expression of a large number of gene products represents a major challenge to the engineering of nitrogen fixation in cereal crops, necessitating reiterative combinatorial assembly cycles to optimize monocistronic gene expression. In this study, we have explored a “fuse-and-cleave” virus-derived polyprotein strategy to reduce gene numbers and achieve balanced expression of protein components required for nitrogenase biosynthesis and activity. After testing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 58 publications
2
67
0
Order By: Relevance
“…Evolutionary, genomic and mechanistic studies suggest that relatively few genetic components might be needed to confer nitrogen-fixation capabilities. In the case of transferring nitrogenase to plants, the restriction of genetic components required was achieved by concatermerizing bacterial genetic units to create a minimal set of three genes that are necessary for the transfer of nitrogen fixation 133 . Moreover, some components of nitrogenase can be stably expressed in yeast and plants 134 .…”
Section: Technologies To Reduce Fertilizer Usementioning
confidence: 99%
“…Evolutionary, genomic and mechanistic studies suggest that relatively few genetic components might be needed to confer nitrogen-fixation capabilities. In the case of transferring nitrogenase to plants, the restriction of genetic components required was achieved by concatermerizing bacterial genetic units to create a minimal set of three genes that are necessary for the transfer of nitrogen fixation 133 . Moreover, some components of nitrogenase can be stably expressed in yeast and plants 134 .…”
Section: Technologies To Reduce Fertilizer Usementioning
confidence: 99%
“…Contemporaneous with that report, the Nfixing genes (nif) of Klebsiella pneumoniae had been inserted into Escherichia coli, causing the nonfixing bacterium capable of growing in the absence of combined N (Dixon & Postgate, 1972). Since then, there has been some research and attempts on introducing N fixation in nonfixing plants and transferring nif genes into heterologous hosts (Yang et al, 2018;Good, 2018;Burén, 2018;Allen et al, 2107;Pérez-González, 2017;López-Torrejón, 2016); however, scientists still lack a comprehensive understanding of the composition of the microorganisms that carry out N fixation processes. To better understand N fixation processes and other biological functions that microorganisms provide plants or their hosts, it is first essential to determine why a microorganism or community evolved, why it persists, and what benefits it imparts to the host itself, other organisms, and the community.…”
Section: What Needs To Be Done?mentioning
confidence: 99%
“…The systemw ith five giant genes showed5 1% nitrogenase activity and supported recombinant E. coli growing in the nitrogen-limited medium. [46] Also, Yang and co-workersd emonstrated that the minimal genes for synthesis of the alternative Fe-dependent nitrogenase in E. coli included the anfHDGK and nifBUSV genes. [47] Recent studies have demonstrated that certain electron-transport chains from plant organelles could functioni ne lectron transfer and provide the reducing equivalents necessary for the activityo fe ither Mo-or Fe-dependent nitrogenase in E. coli.…”
Section: Identifying the Minimal Number Of Nif Genes Required For Nitmentioning
confidence: 99%